Chemical and Biological Quality Control of Drinking Water in Sealed Containers in Phuket province - Binhayeeding, Narisa; Deenamo, Nuramalee; Doloh, Ananya; Poolkua, Jamrat (Journal of Life Science Agriculture and Technology, 2024)
This study aims to investigate the quality of drinking water in sealed containers in terms of chemical and microbiological aspects, including pH, acidity, alkalinity, fluoride, nitrate, coliforms, Escherichia coli, Staphylococcus aureus, and Salmonella spp. for comparison with the legal requirements and standards set by the Ministry of Public Health. It was found that all 10 samples of drinking water in sealed containers met the microbiological and chemical standards at 50%. Among the 5 chemical samples that passed all parameters of the chemical tests, the pH was found to be in the range of 6.8-7.2, no alkalinity was detected, and the fluoride content was less than 5.0 mg/l, with no fluoride detected in one sample and fluoride content ranging from 0.07 to 0.2 mg/l in the rest. Nitrate was not detected in any sample, and the nitrate content was less than 0.4-1.7 mg/l in one sample. Coliform bacteria were detected in one sample at less than 1.1 MPN/ml, while no E. coli, S. aureus, or Salmonella spp. were found in any of the 10 samples. Among the 5 samples that did not meet the criteria up to 50%, it was found that 5 samples had pH values ranging from 5.9 to 6.4, and 2 samples were not tested for alkalinity, with nitrate levels at 4.1 mg/l and coliforms at 3.6 MPN/ml.